Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Challenges in estimating wolf population size using spatial count models and camera trap data - M.V. Boiani; P. Dupont; R. Bischof; O. Friard; F. Bisi; G. Bombieri; S. Calderola; S. Carolfi; C. Chioso; U. Fattori; P. Ferrari; S. Filacorda; et al. (Biological Conservation, 2026)

Incorporation of dose-rate effects into the BIANCA biophysical model and application for space radiation risk assessment - E.I. Canay; M. Carante; A. Casali; E. Bernardini; D. Dondi; Dhanalakshmi Vadivel; L. Cansolino; E. Delgrosso; C. Ferrari; M. Pullia; F. Bonforte; J. Riback; et al. (Life Sciences in Space Research, 2026)

ISRM Suggested Methods for Triaxial Compression Testing of Shales and Mudstones - R. Ewy; E. Fjær; P. Delage; D. Dewhurst; J. Dudley; A. Ferrari; S. Giger; M. Soldal; J. Stenebråten; B. Crawford; S. Fontoura; L. Grande (Rock Mechanics and Rock Engineering, 2026)

Covalently bound Eosin Y on chitosan as a removable photosensitizer for ranitidine degradation - Julieta L. Sacchetto; Alberto M. Barrera Llorente; Marcela Kuhn Beldomenico; José Natera; María J. Gramaglia; Gabriela Porcal; Silvana Plem; Gabriela V. Ferrari; Walter A. Massad (Chemosphere, 2026)

Beyond phosphorus: five years of evidence for nitrate-limited cyanobacterial blooms in a large subtropical river - C. Bueno; N. Muñoz; K. Bombi-Haedo; L. Marín; A. Cabral; G. Ferrari (Hydrobiologia, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Yield and protein gaps in barley: Quantifying nitrogen and sulfur contributions - Federico M. Gomez; Flavio H. Gutiérrez-Boem; Pablo Prystupa; Jorge L. Mercau; Jose J. Boero; Gustavo Ferraris; Leonor G. Abeledo (European Journal of Agronomy, 2026)

Multidisciplinary monitoring of mud volcanoes: a new perspective on fluids and seismicity link from the Salse di Nirano (Italy) - E. Ferrari; A. L. Rizzo; G. Capelli Ghioldi; A. Sciarra; G. Tamburello; F. Viveiros; S. Lovati; M. Massa (Natural Hazards, 2026)
Understanding the relationship between fluids and seismicity is crucial for improving seismic hazard assessment, as fluid migration can play a significant role in earthquake triggering. Here, we present the results from an innovative real-time multiparametric monitoring implemented at the so-called ‘Salse di Nirano’ or mud volcano field (Northern Apennines, Italy), a region of medium to high seismic hazard. The objective is to investigate how geofluid dynamics relate to local seismicity. Two bubbling mud pools were selected for continuous monitoring of mud level, temperature, and electrical conductivity. Additionally, a CO 2 flux station was installed on the field’s edge, where elevated gas emissions are observed. Complementary meteorological and seismic stations track atmospheric conditions and seismic activity. Notably, anomalous shifts in mud pool electrical conductivity and soil CO 2 flux were recorded in temporal correlation with two distinct seismic swarms in 2024, highlighting the potential of fluid-geochemistry monitoring as a tool for tracking subsurface processes linked to seismic unrest.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Novel antimicrobial and antiangiogenic properties from riparin-type benzamides: synthesis, biological evaluation, and docking analysis - Gabriela R. de Sousa; Janaracy L. da Costa Marinho; Pedro Thiago R. de Figueiredo; João Pedro A. Torres; Laísa V. Cordeiro; Luciana Scotti; Edeltrudes O. Lima; Bruna Braga Dantas; Fillipe de Oliveira Pereira; Jailton De Souza-Ferrari; José Maria Barbosa-Filho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Fibroblast Activation Protein (FAP) as a possible therapeutic target in selected canine malignant tumours - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; V. Balbi; G. Bianchi; et al. (Journal of Comparative Pathology, 2025)

Platelet-derived growth factor receptor beta expression in primary and metastatic canine anal sac adenocarcinoma as a potential therapeutic target - A. Verdi; S. Dell'Aere; C. Zamboni; D. Stefanello; R. Ferrari; E. Gariboldi; L. Maniscalco; S. Iussich; C. Romanello; V. Grieco; C. Giudice; C. Recordati; et al. (Journal of Comparative Pathology, 2025)

Analysis of tight junction protein dynamics by immunohistochemistry in porcine intestinal epithelial cells (IPEC-J2) cells exposed to osmotic stress - B. Passeri; P. Borghetti; M. Andrani; M. Di Pentima; A. Luppi; E. De Angelis; V. Cavalli; L. Ferrari; R. Saleri (Journal of Comparative Pathology, 2025)

Splice me up, scotty: Extra domain-B fibronectin in canine tumours puts a spotlight on melanoma - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; A. Verdi; D. Neri; et al. (Journal of Comparative Pathology, 2025)

S12-03 Occupational Exposure to Benzene and Epigenetic Biomarkers of Effect: From Early Discoveries to Emerging Insights - L. Ferrari (Toxicology Letters, 2025)

Short-term personal exposure to multiple air pollutants affects nasal microbiota in school-age children - L. Boniardi; G. Solazzo; C. Favero; L. Campo; L. Ferrari; S. Fustinoni (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Exploring the potency and replenishment of woodfrog disturbance cues, a nonspecific communication system in aquatic species - Gabrielle H. Achtymichuk; Adam L. Crane; Theresa E. Wrynn; Maud C.O. Ferrari (Animal Behaviour, 2025)

A Rapid Method to Identify the Effects of Coastal Artificialization on Posidonia oceanica Meadows in Coves - M. Ferrari; L. Carpi; M. Montefalcone (Estuaries and Coasts, 2025)

Pelletized Organomineral vs. Inorganic Nitrogen and Phosphorus Fertilizers: Impact on Wheat Nutritional Status, Productivity, and Grain Quality - Walter D. Carciochi; Javier L. Ferrari; Luciano Orden; Juan A. Galantini (Journal of Soil Science and Plant Nutrition, 2024)

Deoxynivalenol induces ovarian damage and uterine changes in prepubertal and adult mice - G.A.A. Lemos; J.R. Gerez; J.B. Costa; E.J. Venâncio; M. Souza; P.O. Favaron; J.R. Greghi; E.M. Gloria; L. Staurengo-Ferrari; W.A. Verri; A.P.F.R.L. Bracarense (Toxicon, 2024)

Cytogenetic analysis of meiotic behaviour and stability in a trigeneric hybrid (triticale x trigopiro) - M. Fradkin; E. J. Greizerstein; E. Grassi; V. Ferreira; M. R. Ferrari; L. Poggio (Protoplasma, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Drainage evolution in porous carbonate terrain in semi-arid environments: The role of tectonics and climatic change – The case study of the Boukadir carbonate platform, Algeria - Meriem L. Moulana; Marthe Lefevre; Aurélia Hubert-Ferrari (Geomorphology, 2024)

The use of fishery and aquaculture by-products with Nannochloropsis sp. allows total dietary replacement of wild-caught fishmeal, fish oil and soy protein in European sea bass juveniles - A. Marchi; E. Benini; F. Dondi; M.G. Ferrari; D. Scicchitano; G. Palladino; M. Candela; R. Cerri; A. Di Biase; A.J. Vizcaíno; F.J. Alarcón-López; F.G. Acién; et al. (Aquaculture, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Thermal tolerance as a driver of reef fish community structure at the isolated tropical Mid-Atlantic Ridge Islands - Débora S. Ferrari; Lucas T. Nunes; Kirsty L. Jones; Carlos E.L. Ferreira; Sergio R. Floeter (Marine Environmental Research, 2024)

Insights from an extensive triaxial testing campaign on a shale for comparative site characterization of a deep geological repository - E. Crisci; S.B. Giger; L. Laloui; A. Ferrari; R. Ewy; R. Stankovic; J. Stenebråten; K. Halvorsen; M. Soldal (Geomechanics for Energy and the Environment, 2024)

Sub-lethal effects of the insecticide, imidacloprid, on the responses of damselfly larvae to chemosensory cues indicating predation risk - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Douglas P. Chivers; Maud C.O. Ferrari (Chemosphere, 2024)

Evapotranspiration of an abandoned grassland in the Italian Alps: Modeling the impact of shrub encroachment - Davide Gisolo; Ivan Bevilacqua; Alessio Gentile; Justus van Ramshorst; Davide L. Patono; Claudio Lovisolo; Maurizio Previati; Davide Canone; Stefano Ferraris (Journal of Hydrology, 2024)

Photosensitized oxygenation reactions as an alternative towards the degradation of fenamates and related pollutants using visible light - Eduardo L. Gutiérrez; Julieta Sacchetto; Francisco Boscá; M. Luisa Marín; Walter Massad; M. Paulina Montaña; Sandra Miskoski; Gabriela V. Ferrari (Journal of Water Process Engineering, 2024)

Enteric associated T-cell lymphoma in a mule - Giovanna G. de Souza; Zara A. Lacerda; Fernanda B.C. de Moura; Isabeli J. Contel; Shéron L. de Oliveira; Lorena C. Ferrari; Emanuel V.P. Apolonio; Juliana de M. Alonso; Ana Liz G. Alves; Noeme S. Rocha (Journal of Equine Veterinary Science, 2024)

Comparison of cytologicAL and histologicAL classification systems for the detection of nodal metastases of canine mast cell tumours - A. Renzi; M.G. Ferrari; R. Zaccone; L. Marconato; C. Agnoli; S. Zanardi; S. Sabattini (Journal of Comparative Pathology, 2024)

Implementation of Soreide and Whitson EoS in a GPU-based reservoir simulator - P. Panfili; L. Patacchini; A. Ferrari; T. Garipov; K. Esler; A. Cominelli (Computational Geosciences, 2024)

Effect of high-voltage electrical discharge (HVED) at high frequency on vacuum freeze-drying time and physicochemical properties of blueberries - R. Díaz-Álvarez; S. Carpentieri; G. Ferrari; G. Pataro; L. Segura-Ponce (Journal of Food Engineering, 2024)

A Global Systematic Literature Review of Ecosystem Services in Reef Environments - Vinicius J. Giglio; Anaide W. Aued; Cesar A. M. M. Cordeiro; Linda Eggertsen; Débora S. Ferrari; Leandra R. Gonçalves; Natalia Hanazaki; Osmar J. Luiz; André L. Luza; Thiago C. Mendes; Hudson T. Pinheiro; Bárbara Segal; et al. (Environmental Management, 2024)

Exposure to the insecticide, imidacloprid, impairs predator-recognition learning in damselfly larvae - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Maud C.O. Ferrari; Douglas P. Chivers (Environmental Pollution, 2024)

CFD simulation of a high-shear mixer for food emulsion production - Marco Ferrari; Gianluca Boccardo; Antonio Buffo; Marco Vanni; Daniele L. Marchisio (Journal of Food Engineering, 2023)

Ethanol Production from Eucalyptus Sawdust Following Sequential Alkaline Thermochemical Pretreatment with Recovery of Extractives - M. Guigou; S. Moure; F. Bermúdez; L. Clavijo; M. N. Cabrera; L. Xavier; M. D. Ferrari; C. Lareo (BioEnergy Research, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Acute and subchronic effects of ibuprofen on the ten spotted live-bearer fish Cnesterodon decemmaculatus (Jenyns, 1842) - L.B. Campos; A.A. González Núñez; M.J. Palacio; J.P. Ferro; P.M. Castañé; L. Ferrari; N.A. Ossana (Chemosphere, 2023)

Hybrid multi-core shell magnetic nanoparticles for wet peroxide oxidation of paracetamol: Application in synthetic and real matrices - Adriano S. Silva; Fernanda F. Roman; Arnaldo V. Dias; Jose L. Diaz de Tuesta; Alexandre Narcizo; Ana Paula F. da Silva; Ihsan Çaha; Francis Leonard Deepak; Manuel Bañobre-López; Ana M.C. Ferrari; Helder T. Gomes (Journal of Environmental Chemical Engineering, 2023)

Exploring porcine kidney explants as a model for the study of nephrotoxins and the therapeutic potential of phytic acid - W.G. Suhett; J.R. Gerez; M.S. Hohmann; L. Staurengo-Ferrari; W.A. Verri; F.H.O. Pinho; L.D. de Barros; S.T. Cardim; K.M.C. Flaiban; Ana Paula F.R.L. Bracarense (Environmental Toxicology and Pharmacology, 2023)

Mycobacterium avium subsp. paratuberculosis and Crohn’s disease: characterization of the interaction with different aspects of the disease - I. F. Espeschit; D. S. S. Bastos; A. Fonseca Junior; S. A. Cardoso; M. L. A. Ferrari; M. A. S. Moreira (Brazilian Journal of Microbiology, 2023)

Non-toxic acid-free glyoxal fixative for veterinary histopathology, immunohistochemistry and molecular analysis - V. Zappulli; F. Torrigiani; P. Detillo; S. Iussich; M. Rondena; C. Gola; L. MInoli; E. Morello; E.I. Ferraris; A. Rigillo; B. Bussolati (Journal of Comparative Pathology, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

TMS-evoked EEG potentials demonstrate altered cortical excitability in migraine with aura - Robert M. Helling; Matthijs J. L. Perenboom; Prisca R. Bauer; Johannes A. Carpay; Josemir W. Sander; Michel D. Ferrari; Gerhard H. Visser; Else A. Tolner (Brain Topography, 2023)
Migraine is associated with altered sensory processing, that may be evident as changes in cortical responsivity due to altered excitability, especially in migraine with aura. Cortical excitability can be directly assessed by combining transcranial magnetic stimulation with electroencephalography (TMS-EEG). We measured TMS evoked potential (TEP) amplitude and response consistency as these measures have been linked to cortical excitability but were not yet reported in migraine. We recorded 64-channel EEG during single-pulse TMS on the vertex interictally in 10 people with migraine with aura and 10 healthy controls matched for age, sex and resting motor threshold. On average 160 pulses around resting motor threshold were delivered through a circular coil in clockwise and counterclockwise direction. Trial-averaged TEP responses, frequency spectra and phase clustering (over the entire scalp as well as in frontal, central and occipital midline electrode clusters) were compared between groups, including comparison to sham-stimulation evoked responses. Migraine and control groups had a similar distribution of TEP waveforms over the scalp. In migraine with aura, TEP responses showed reduced amplitude around the frontal and occipital N100 peaks. For the migraine and control groups, responses over the scalp were affected by current direction for the primary motor cortex, somatosensory cortex and sensory association areas, but not for frontal, central or occipital midline clusters. This study provides evidence of altered TEP responses in-between attacks in migraine with aura. Decreased TEP responses around the N100 peak may be indicative of reduced cortical GABA-mediated inhibition and expand observations on enhanced cortical excitability from earlier migraine studies using more indirect measurements.

Textile microfibers in wild Antarctic whelk Neobuccinum eatoni (Smith, 1875) from Terra Nova Bay (Ross Sea, Antarctica) - E. Bergami; E. Ferrari; M.G.J. Löder; G. Birarda; C. Laforsch; L. Vaccari; I. Corsi (Environmental Research, 2023)

A review of the main methods for composite adsorbents characterization - Mateus T. Nazari; Carlos Schnorr; Cesar V. T. Rigueto; Ingridy Alessandretti; Flávia Melara; Nathália F. da Silva; Larissa Crestani; Valdecir Ferrari; Julien Vieillard; Guilherme L. Dotto; Luis F. O. Silva; Jeferson S. Piccin (Environmental Science and Pollution Research, 2022)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Digital biomarkers and sex impacts in Alzheimer’s disease management — potential utility for innovative 3P medicine approach - Robbert L. Harms; Alberto Ferrari; Irene B. Meier; Julie Martinkova; Enrico Santus; Nicola Marino; Davide Cirillo; Simona Mellino; Silvina Catuara Solarz; Ioannis Tarnanas; Cassandra Szoeke; Jakub Hort; et al. (EPMA Journal, 2022)
Digital biomarkers are defined as objective, quantifiable physiological and behavioral data that are collected and measured by means of digital devices. Their use has revolutionized clinical research by enabling high-frequency, longitudinal, and sensitive measurements. In the field of neurodegenerative diseases, an example of a digital biomarker-based technology is instrumental activities of daily living (iADL) digital medical application, a predictive biomarker of conversion from mild cognitive impairment (MCI) due to Alzheimer’s disease (AD) to dementia due to AD in individuals aged 55 + . Digital biomarkers show promise to transform clinical practice. Nevertheless, their use may be affected by variables such as demographics, genetics, and phenotype. Among these factors, sex is particularly important in Alzheimer’s, where men and women present with different symptoms and progression patterns that impact diagnosis. In this study, we explore sex differences in Altoida’s digital medical application in a sample of 568 subjects consisting of a clinical dataset (MCI and dementia due to AD) and a healthy population. We found that a biological sex-classifier, built on digital biomarker features captured using Altoida’s application, achieved a 75% ROC-AUC (receiver operating characteristic — area under curve) performance in predicting biological sex in healthy individuals, indicating significant differences in neurocognitive performance signatures between males and females. The performance dropped when we applied this classifier to more advanced stages on the AD continuum, including MCI and dementia, suggesting that sex differences might be disease-stage dependent. Our results indicate that neurocognitive performance signatures built on data from digital biomarker features are different between men and women. These results stress the need to integrate traditional approaches to dementia research with digital biomarker technologies and personalized medicine perspectives to achieve more precise predictive diagnostics, targeted prevention, and customized treatment of cognitive decline.

Effects of application rate on spray deposition, stink bug control, and yield in soybean crops - José L. C. Santos-Júnior; Carlos G. Raetano; Fernando K. de Carvalho; Pedro J. Ferreira-Filho; Júlio C. Guerreiro; Samuel Ferrari; Vagner Nascimento; Rafael S. Tomaz; Agatha S. Argioli; Evandro P. Prado (Phytoparasitica, 2022)

The predictive capacity of the high resolution weather research and forecasting model: a year-long verification over Italy - L. Apicella; S. Puca; M. Lagasio; A. N. Meroni; M. Milelli; N. Vela; V. Garbero; L. Ferraris; A. Parodi (Bulletin of Atmospheric Science and Technology, 2021)
Numerical models are operationally used for weather forecasting activities to reduce the risks of several hydro-meteorological disasters. The overarching goal of this work is to evaluate the Weather Research and Forecasting (WRF) model predictive capabilities over the Italian national territory in the year 2018, in two specific cloud resolving configurations. The validation is carried out with a fuzzy logic approach, by comparing the precipitation predicted by the WRF model, and the precipitation observed by the national network. The fuzzy logic technique, by considering different intensity thresholds, allows to identify the reliable spatial scales of the forecasts. The same approach is applied to evaluate the performances of COSMO-2I model, a state-of-the-art numerical model configuration used for operational activities. For the entire year, except for summer, the model predictive capabilities are high, with useful forecasts for structures of medium intensities down to O (10 km) length scales. In summer the skills decrease mainly because of localization errors. The work aims to provide a robust evaluation of the forecast performances of another convection permitting operational meteorological models currently available in Italy.

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

New Horizons on Non-invasive Brain Stimulation of the Social and Affective Cerebellum - Z. Cattaneo; C. Ferrari; A. Ciricugno; E. Heleven; D. J. L. G. Schutter; M. Manto; F. Van Overwalle (The Cerebellum, 2021)

Physical activity for cancer patients during COVID-19 pandemic: a call to action - Leandro F. M. Rezende; Dong Hoon Lee; Gerson Ferrari; José Eluf-Neto; Edward L. Giovannucci (Cancer Causes & Control, 2021)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seismological analyses of the seismic microzonation of 138 municipalities damaged by the 2016–2017 seismic sequence in Central Italy - E. Priolo; F. Pacor; D. Spallarossa; G. Milana; G. Laurenzano; M. A. Romano; C. Felicetta; S. Hailemikael; F. Cara; G. Di Giulio; G. Ferretti; C. Barnaba; et al. (Bulletin of Earthquake Engineering, 2020)
This paper describes the seismological analyses performed within the framework of the seismic microzonation study for the reconstruction of 138 municipalities damaged by the 2016–2017 sequence in Central Italy. Many waveforms were recorded over approximately 15 years at approximately 180 instrumented sites equipped with permanent or temporary stations in an area that includes all the damaged localities. Site response was assessed using earthquake and noise recordings at the selected stations through different parameters, such as spectral amplification curves, fundamental resonance frequencies, site-specific response spectra, and average amplification factors. The present study was a collaboration of many different institutions under the coordination of the Italian Center for Seismic Microzonation and its applications . The results were homogenized and gathered into site-specific forms, which represent the main deliverable for the benefit of Italian Civil Protection. It is remarkable that the bulk of this study was performed in a very short period (approximately 2 months) to provide quantitative information for detailed microzonation and future reconstruction of the damaged municipalities.

Proportional fitness loss and the timing of defensive investment: a cohesive framework across animals and plants - Michael J. Sheriff; John L. Orrock; Maud C. O. Ferrari; Richard Karban; Evan L. Preisser; Andrew Sih; Jennifer S. Thaler (Oecologia, 2020)

Comparative diversity of anemone-associated fishes and decapod crustaceans in a Belizean coral reef and seagrass system - Rohan M. Brooker; William E. Feeney; Tiffany L. Sih; Maud. C. O. Ferrari; Douglas P. Chivers (Marine Biodiversity, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Conducting groundwater monitoring studies in Europe for pesticide active substances and their metabolites in the context of Regulation (EC) 1107/2009 - Anne Louise Gimsing; Jutta Agert; Nicole Baran; Arnaud Boivin; Federico Ferrari; Richard Gibson; Lisa Hammond; Florian Hegler; Russell L. Jones; Wolfram König; Jenny Kreuger; Ton van der Linden; et al. (Journal of Consumer Protection and Food Safety, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Diallelic Analysis of Endogamic Maize Lines with Emphasis on Agronomic Traits of Tassel in Different Environments - D. Barreta; M. Nardino; V. A. Konflanz; A. J. de Pelegrin; M. Ferrari; V. J. Szareski; I. R. Carvalho; V. Q. de Souza; A. C. de Oliveira; L. C. da Maia (Journal of Crop Science and Biotechnology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Marine infrastructure supports abundant, diverse fish assemblages at the expense of beta diversity - A. G. Porter; R. L. Ferrari; B. P. Kelaher; S. D. A. Smith; R. A. Coleman; M. Byrne; W. Figueira (Marine Biology, 2018)

Key drivers of effectiveness in small marine protected areas - John W. Turnbull; Yasmina Shah Esmaeili; Graeme F. Clark; Will F. Figueira; Emma L. Johnston; Renata Ferrari (Biodiversity and Conservation, 2018)

Development of Transgenic Sugarcane Resistant to Sugarcane Borer - Plinio T. Cristofoletti; Edson L. Kemper; Adriana N. Capella; Sandra R. Carmago; Juliana L. Cazoto; Fernanda Ferrari; Tederson L. Galvan; Luciane Gauer; Gustavo A. Monge; Marcelo A. Nishikawa; Nicolas Z. Santos; Altair A. Semeao; et al. (Tropical Plant Biology, 2018)

Environmental control of malting barley response to nitrogen in the Pampas, Argentina - P. Prystupa; G. Ferraris; L. Ventimiglia; T. Loewy; L. Couretot; R. Bergh; F. Gómez; F. H. Gutierrez Boem (International Journal of Plant Production, 2018)

CHIPS: an Extensible Toolbox for Cellular and Hemodynamic Two-Photon Image Analysis - Matthew J. P. Barrett; Kim David Ferrari; Jillian L. Stobart; Martin Holub; Bruno Weber (Neuroinformatics, 2018)

Nucleolar activity in Triticum x Thinopyrum hybrids with different ploidy level - M. Fradkin; E. J. Greizerstein; M. R. Ferrari; L. Poggio (Plant Biosystems, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Polymorphisms of dopamine receptor genes and risk of visual hallucinations in Parkinson’s patients - M Ferrari; C Comi; F Marino; L Magistrelli; F De Marchi; R Cantello; G Riboldazzi; G Bono; M Cosentino (European Journal of Clinical Pharmacology, 2016)

Asymmetric competition prevents the outbreak of an opportunistic species after coral reef degradation - Manuel González-Rivero; Yves-Marie Bozec; Iliana Chollett; Renata Ferrari; Christine H. L. Schönberg; Peter J. Mumby (Oecologia, 2016)

Clinical, hematological, biochemical, and ultrasonographic aspects of Platynosomum sp. (Trematoda: Dicrocoeliidae) infection of captive Callithrix penicillata - Mariana Portugal Mattioli; Juliana dos Santos Batista; Marlon Ferrari; Giane Regina Paludo; Cecília Azevedo Dias; Estevam G. L. Hoppe; Gino Chaves da Rocha; Rafael Veríssimo Monteiro (Primates, 2016)

An Overview of an Acidic Uranium Mine Pit Lake (Caldas, Brazil): Composition of the Zooplankton Community and Limnochemical Aspects - Carla R. Ferrari; Heliana de Azevedo; Maria José S. Wisniewski; Suzelei Rodgher; Cláudio Vitor Roque; Marcos Roberto L. Nascimento (Mine Water and the Environment, 2015)

Individual vs. social learning of predator information in fish: does group size affect learning efficacy? - Anthony G. E. Mathiron; Adam L. Crane; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Toxicity and persistence of three pyrethroids for the control of cereal bugs on common wheat - Marco G. Pansa; Massimo Blandino; Barbara L. Ingegno; Ester Ferrari; Amedeo Reyneri; Luciana Tavella (Journal of Pest Science, 2015)

Review of West Nile virus epidemiology in Italy and report of a case of West Nile virus encephalitis - Serena Delbue; Pasquale Ferrante; Sara Mariotto; Gianluigi Zanusso; Antonino Pavone; Mauro Chinaglia; Roberto L’Erario; Salvatore Monaco; Sergio Ferrari (Journal of NeuroVirology, 2014)

Social learning of predators by coral reef fish: does observer number influence acquisition of information? - R. P. Manassa; M. I. McCormick; D. L. Dixson; M. C. O. Ferrari; D. P. Chivers (Behavioral Ecology and Sociobiology, 2014)

Bronchial microbiome of severe COPD patients colonised by Pseudomonas aeruginosa - L. Millares; R. Ferrari; M. Gallego; M. Garcia-Nuñez; V. Pérez-Brocal; M. Espasa; X. Pomares; C. Monton; A. Moya; E. Monsó (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Modeling the spread of invasive species using dynamic network models - Joseph R. Ferrari; Evan L. Preisser; Matthew C. Fitzpatrick (Biological Invasions, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Effects of turbidity and an invasive waterweed on predation by introduced largemouth bass - Maud C. O. Ferrari; Lynn Ranåker; Kelly L. Weinersmith; Matthew J. Young; Andrew Sih; J. Louise Conrad (Environmental Biology of Fishes, 2014)

Quantitative panbiogeography: was the congruence problem solved? - Augusto Ferrari; Kim R. Barão; Felipe L. Simões (Systematics and Biodiversity, 2013)

Genetic diversity of the rare and endangered meadow violet ( Viola pumila Chaix) at the southern margin of its range - F. Buldrini; L. Conte; D. Dallai; C. Ferrari (Plant Biosystems, 2013)

Retention of acquired predator recognition among shy versus bold juvenile rainbow trout - G. E. Brown; M. C. O. Ferrari; P. H. Malka; L. Fregeau; L. Kayello; D. P. Chivers (Behavioral Ecology and Sociobiology, 2013)

Assessing and promoting old-growthness of forest stands: Lessons from research in Italy - A. Barbati; R. Salvati; B. Ferrari; D. Di Santo; A. Quatrini; L. Portoghesi; D. Travaglini; F. Iovino; S. Nocentini (Plant Biosystems, 2012)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

Energy balance of juvenile Cyprinus carpio after a short-term exposure to sublethal water-borne cadmium - L. Ferrari; B. L. Eissa; A. Salibián (Fish Physiology and Biochemistry, 2011)

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

Intake of aflatoxins through the consumption of peanut products in Brazil - I.C.O. Magrine; S.S.C. Ferrari; G.F. Souza; L. Minamihara; C. Kemmelmeier; E. Bando; M. Machinski (Food Additives & Contaminants Part B-Surveillance, 2011)

Use of a comprehensive numerical model to improve biventricular pacemaker temporization in patients affected by heart failure undergoing to CRT-D therapy - A. Di Molfetta; L. Santini; G. B. Forleo; M. Cesario; C. Tota; M. Sgueglia; D. Sergi; G. Ferrari; F. Romeo (Medical & Biological Engineering & Computing, 2010)

Swine virus-specific cytotoxic cells producing IFNγ under different conditions of virus antigenic stimulation - L. Ferrari; E. De Angelis; P. Martelli; P. Borghetti (Veterinary Research Communications, 2010)

Relationship between body fat and body condition score and their effects on estrous cycles of the Standardbred maiden mare - I. Vecchi; A. Sabbioni; E. Bigliardi; G. Morini; L. Ferrari; F. Di Ciommo; P. Superchi; E. Parmigiani (Veterinary Research Communications, 2010)

Copper (II) adsorption studies using models of synthetic humic acids - Marcilene Ferrari Barriquello; N. Consolin-Filho; E. R. Carvalho; M. Y. Kamogawa; L. Martin-Neto (Environmental Chemistry Letters, 2010)

Quantitative Behavioral Parameters as Toxicity Biomarkers: Fish Responses to Waterborne Cadmium - B. L. Eissa; N. A. Ossana; L. Ferrari; A. Salibián (Archives of Environmental Contamination and Toxicology, 2010)

Monitoring and assessing old‐growth forest stands by plot sampling - P. Corona; C. Blasi; G. Chirici; L. Facioni; L. Fattorini; B. Ferrari (Plant Biosystems, 2010)

α- and β-Adducin polymorphisms affect podocyte proteins and proteinuria in rodents and decline of renal function in human IgA nephropathy - Mara Ferrandi; Daniele Cusi; Isabella Molinari; Lucia Del Vecchio; Cristina Barlassina; Maria Pia Rastaldi; Francesco Paolo Schena; Fabio Macciardi; Carmelita Marcantoni; Dario Roccatello; Luanne L. Peters; Silvia Armelloni; et al. (Journal of Molecular Medicine, 2010)

Cellular immune response and immunotoxicity induced by DON (deoxynivalenol) in piglets - L. Ferrari; A. M. Cantoni; P. Borghetti; E. De Angelis; A. Corradi (Veterinary Research Communications, 2009)

Geographic distribution and population characteristics of the endangered white-fronted spider monkey (Ateles marginatus) on the lower Tapajós River in central Brazilian Amazonia - André L. Ravetta; Stephen F. Ferrari (Primates, 2009)

Sensitivity of preparasitic stages of Chordodes nobilii (Gordiida, Nematomorpha) to malathion - Cecilia L. Achiorno; Cristina De Villalobos; Lucrecia Ferrari (Ecotoxicology, 2009)

Applications of flow cytometry in environmental microbiology and biotechnology - Peter L. Bergquist; Elizabeth M. Hardiman; Belinda C. Ferrari; Tristrom Winsley (Extremophiles, 2009)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)

Temporal Decrease of Trivalent Chromium Concentration in a Standardized Algal Culture Medium: Experimental Results and Implications for Toxicity Evaluation - Davide A. L. Vignati; Mamadou L. Beye; Janusz Dominik; Anna O. Klingemann; Montserrat Filella; Andrzej Bobrowski; Benoît J. Ferrari (Bulletin of Environmental Contamination and Toxicology, 2008)

The role of hepatic, renal and intestinal gluconeogenic enzymes in glucose homeostasis of juvenile rainbow trout - Séverine Kirchner; Stéphane Panserat; Pauline L. Lim; Sadasivam Kaushik; Ronaldo P. Ferraris (Journal of Comparative Physiology B, 2008)

Closed-tube DNA extraction using a thermostable proteinase is highly sensitive, capable of single parasite detection - B. C. Ferrari; M. L. Power; P. L. Bergquist (Biotechnology Letters, 2007)

Genetic variation in the effect of a facultative symbiont on host-plant use by pea aphids - Julia Ferrari; Claire L. Scarborough; H. Charles J. Godfray (Oecologia, 2007)

Parameters for Evaluating the Cell-Mediated Immune Response During Viral Infection: Diagnostic and Prognostic Applications - A. Corradi; L. Ferrari; P. Borghetti (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Behavioral Alterations in Juvenile Cyprinus carpio (Linnaeus, 1758) Exposed to Sublethal Waterborne Cadmium - B. L. Eissa; A. Salibián; L. Ferrari (Bulletin of Environmental Contamination and Toxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

Intake of fruits and vegetables and risk of cancer of the upper aero-digestive tract: the prospective EPIC-study - Heiner Boeing; Thomas Dietrich; Kurt Hoffmann; Tobias Pischon; Pietro Ferrari; Petra H. Lahmann; Marie Christine Boutron-Ruault; Francoise Clavel-Chapelon; Naomi Allen; Tim Key; Guri Skeie; Eiliv Lund; et al. (Cancer Causes & Control, 2006)

Effect of Weaning and Vaccinations on Immune and Hormonal Parameters in Neonatal Piglets - P. Borghetti; L. Ferrari; V. Cavalli; E. De Angelis; R. Saleri; A. Corradi; P. Martelli (Veterinary Research Communications, 2006)

Bone Mineral Density in Two Boxer Dogs Affected by Moderate to End-stage Chronic Renal Failure - A. Zotti; M. Caldin; E. Vettorato; V. Ferrari; L. Cavicchioli; D. Bernardini (Veterinary Research Communications, 2006)

Study on the Virulence, Cell-mediated Immune Response and Histolesivity of Three Field PRRSV Strains with an ORF 5 Genetic Variation - A. Corradi; M. Ferrari; A. M. Cantoni; C. Robotti; L. Alborali; R. Di Lecce; P. Candotti; G. P. Sandri; P. Borghetti (Veterinary Research Communications, 2005)

Characterization and metal affinity of Tirofiban, a pharmaceutical compound used in acute coronary syndromes - E. Ferrari; L. Menabue; M. Saladini (BioMetals, 2004)

Identification of the breast boundary in mammograms using active contour models - R. J. Ferrari; A. F. Frère; R. M. Rangayyan; J. E. L. Desautels; R. A. Borges (Medical & Biological Engineering & Computing, 2004)

Electron transfer in crystals of the binary and ternary complexes of methylamine dehydrogenase with amicyanin and cytochrome c551i as detected by EPR spectroscopy - Davide Ferrari; Marilena Di Valentin; Donatella Carbonera; Angelo Merli; Zhi-wei Chen; F. Scott Mathews; Victor L. Davidson; Gian Luigi Rossi (JBIC Journal of Biological Inorganic Chemistry, 2004)

Sigmoidal exsolution by internal shear stress in pyroxenes from chondritic meteorites - C. Ferraris; L. Folco; M. Mellini (Physics and Chemistry of Minerals, 2003)

Geophagy as a Correlate of Folivory in Red-Handed Howler Monkeys (Alouatta belzebul) from Eastern Brazilian Amazonia - Luciane L. de Souza; Stephen F. Ferrari; Marcondes L. da Costa; Dirse C. Kern (Journal of Chemical Ecology, 2002)

Tadpoles Assay: Its Application to a Water Toxicity Assessment of a Polluted Urban River - S. O. Demichelis; F. R. de la Torre; L. Ferrari; M. E. García; A. Salibián (Environmental Monitoring and Assessment, 2001)

Is a Kit for Identification of Clinical Yeasts Correctly Evaluated When Released onto the Market? - A. M. Tortorano; F. Barchiesi; E. Manso; M. T. Montagna; C. Farina; L. Ferrari; A. Raballo; A. Grancini; G. Lombardi (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Changing Concentrations of Cu, Zn, Cd and Pb in a High Altitude Peat Bog from Bolivia during the Past Three Centuries - E. Espi; C.F. Boutron; S. Hong; M. Pourchet; C. Ferrari; W. Shotyk; L. Charlet (Water, Air, & Soil Pollution, 1997)

Volume and Ion Regulation During Repeated Exposure to Temperature Change: Physiological Divergence in Trans‐Isthmian Cognate Pairs and Latitudinally Distant Populations of Decapod Crustacea - J. D. Ferraris; J. L. Norenburg (Marine Ecology, 1997)
When the Isthmus of Panama emerged as a land bridge, it set the stage for allopatric speciation in the marine fauna. In the present study Pacific and Atlantic populations of three cognate pairs of crabs were used to discern whether physiological divergence has occurred as a result of exposure to different thermal regimes in habitats and in the putative absence of gene flow. Additional comparison was made with Belize and Florida populations of the Atlantic Panama cognate. This was done to test the strength of correlation between physiological divergence and exposure to different thermal regimes in populations that potentially form a common genetic pool. Water temperatures decrease periodically in Pacific Panama and Florida but not in Atlantic Panama or Belize. Physiological divergence in volume and ion regulation was assessed in response to repeated exposure to either control and decreased temperature or to control and increased temperature. Results indicate that exposure to naturally occurring decreased temperatures in habitats has resulted in divergence. This divergence is demonstrated both in enhanced ability to regulate volume at decreased temperature and impaired ability to regulate volume at elevated temperature.

Oxygen Uptake During Repeated Exposure to Temperature Change: Physiological Divergence in Panamanian Cognate Pairs and Latitudinally Distant Populations of Decapod Crustacea - J. D. Ferraris; J. L. Norenburg (Marine Ecology, 1997)
The emergence of the Isthmus of Panama subdivided the amphi‐American biota. In the present study, Pacific and Atlantic populations of four cognate pairs of crabs were used to discern whether exposure to different thermal regimes in habitats, in the putative absence of gene flow, has resulted in physiological divergence. Populations that potentially form a common genetic pool were also used; these were populations of the Atlantic Panama cognate that occur in Belize and Florida. Decreases in water temperature occur periodically in Pacific Panama and Florida, but not in Atlantic Panama or Belize. In this study, physiological divergence in oxygen uptake was assessed in response to repeated exposure to either control and decreased temperature or control and increased temperature. Results indicate that, in only some of the genera tested, exposure to decreases in habitat temperature has resulted in divergence. Partial support is found for the corollary that adaptation to an environment with periods of decreased temperature results in reduced compensation during exposure to elevated temperature.

Cytogenetic biomonitoring of styrene-exposed plastic boat builders - M. Artuso; G. Angotzi; S. Bonassi; S. Bonatti; M. De Ferrari; D. Gargano; L. Lastrucci; L. Miligi; C. Sbrana; A. Abbondandolo (Archives of Environmental Contamination and Toxicology, 1995)

Isolation and characterization of cytopathic strains of rotavirus from rabbits - G. Castrucci; M. Ferrari; F. Frigeri; V. Cilli; L. Perucca; G. Donelli (Archives of Virology, 1985)

Reactivation in calves ofBovid herpesvirus 2 latent infection - G. Castrucci; M. Ferrari; F. Frigeri; S. Ranucci; V. Cilli; B. Tesei; L. Rampichini (Archives of Virology, 1982)